Aligning and reconciling: building project capabilities for digital delivery - Lobo,S; Whyte,J (Research Policy, 2017)
Digital delivery of complex projects, using integrated software and processes, is an important emerging phenomenon as it transforms relationships across the associated ecology of project-based firms. Our study analyses how a project-based firm, ‘Global Engineering’, builds new project capabilities for digital delivery through work on three major road and railway infrastructure projects. We find that it seeks to: (1) align the project set-up with the firm’s existing capabilities; and (2) reconcile differing agendas and capabilities in collaborating firms across the project ecology. Here, aligning involves influencing the set-up of digital delivery and renegotiating that set-up during project implementation; and reconciling involves managing across multiple digital systems; accommodating and learning other firms’ software and processes; and using digital technologies to create shared identity across the firms involved in delivery. We argue that creating relative stability enables firms to use existing, and build new, project capabilities, and hence aligning and reconciling are important to project-based firms in environments where there is high interdependence across heterogeneous firms and rapid technological change. We find that building these capabilities involves both ‘economies of repetition’ and ‘economies of recombination’; the former enabling the firm to capture value by mobilizing existing resources and the latter, requiring additional work to re-combine existing and new resources. Our study thus provides insight into how project-based firms build project capabilities for the digital delivery of complex projects in order to remain competitive in their existing markets, and has broader implications for learning in the project ecologies associated with these projects.